2020
DOI: 10.1038/s41598-020-73049-5
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the tilt of a moving domain wall shows precession-free dynamics in compensated ferrimagnets

Abstract: One fundamental obstacle to efficient ferromagnetic spintronics is magnetic precession, which intrinsically limits the dynamics of magnetic textures. We experimentally demonstrate that this precession vanishes when the net angular momentum is compensated in domain walls driven by spin–orbit torque in a ferrimagnetic GdFeCo/Pt track. We use transverse in-plane fields to provide a robust and parameter-free measurement of the domain wall internal magnetisation angle, demonstrating that, at the angular compensatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…We cannot exclude additional contributions as, for example, from inversion symmetry breaking by the (small) concentration gradient in our samples. Experiments on FePt [10] and GdFeCo [29,30] have already shown that a composition gradient can play an important role for the generation of torques [10,24] and "bulk DMI" [29,30] in single layers of such magnetic alloys. In the large family of magnetic rare-earth alloys and other 5d magnetic materials, the existence of these different SOC-based mechanisms related to the absence of inversion symmetry and generating spin currents, spin torques and DMI in single layers in the absence of additional HM layers, is of great interest.…”
Section: Effmentioning
confidence: 99%
See 2 more Smart Citations
“…We cannot exclude additional contributions as, for example, from inversion symmetry breaking by the (small) concentration gradient in our samples. Experiments on FePt [10] and GdFeCo [29,30] have already shown that a composition gradient can play an important role for the generation of torques [10,24] and "bulk DMI" [29,30] in single layers of such magnetic alloys. In the large family of magnetic rare-earth alloys and other 5d magnetic materials, the existence of these different SOC-based mechanisms related to the absence of inversion symmetry and generating spin currents, spin torques and DMI in single layers in the absence of additional HM layers, is of great interest.…”
Section: Effmentioning
confidence: 99%
“…Such a gradient can break the inversion symmetry and generate a “bulk Rashba effect.” [ 10,22 ] Notably, Dzyaloshinskii–Moriya interactions (DMI), which is another consequence of SOC and lack of inversion symmetry, have been recently observed and related to composition gradients in single layers of GdFeCo. [ 24,29,30 ]…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…with σ the energy per unit area of the wall, k B the Boltzmann constant and t the thickness of the sample. Table I shows the values of L c in our system at different temperatures, calculated using the energy σ = 4∆K eff [30] with a typical domain wall width parameter ∆ ≈ 15 nm [31][32][33].…”
Section: B Determination Of the Structure Factor Parametersmentioning
confidence: 99%
“…Secondly, the reduced net angular momentum leads to drastically faster magnetic dynamics. Promising theoretical results and experimental observations have been recently obtained in such multi-lattice magnetic systems [2,3], multi-layers architectures [4][5][6], or synthetic alloys [7][8][9][10][11][12][13]. In particular, it has been * joao.sampaio@universite-paris-saclay.fr shown that the antiferromagnetic coupling between sublattices brings the characteristic frequency of magnetisation dynamics up to the THz range [14][15][16][17][18].…”
mentioning
confidence: 99%